2017
DOI: 10.1177/1010428317694327
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing of the TP53 gene reveals a potential risk allele for non–small cell lung cancer and supports the negative prognostic value of TP53 variants

Abstract: The TP53 gene remains the most frequently altered gene in human cancer, of which variants are associated with cancer risk, therapy resistance, and poor prognosis in several tumor types. To determine the true prognostic value of TP53 variants in non-small cell lung cancer, this study conducted further research, particularly focusing on subtype and tumor stage. Therefore, we determined the TP53 status of 97 non-small cell lung cancer adenocarcinoma patients using next generation deep sequencing technology and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Some studies of NSCLC of mixed histologic subtypes do not show any prognostic impact of mutated TP53 [32,33]. Other reports, including ours, show worse survival in lung adenocarcinoma patients with mutations in TP53 [34,35]. However, separating the true prognostic and predictive impact of TP53, in relation to adjuvant therapy, has proven to be difficult [36].…”
Section: Discussionmentioning
confidence: 52%
“…Some studies of NSCLC of mixed histologic subtypes do not show any prognostic impact of mutated TP53 [32,33]. Other reports, including ours, show worse survival in lung adenocarcinoma patients with mutations in TP53 [34,35]. However, separating the true prognostic and predictive impact of TP53, in relation to adjuvant therapy, has proven to be difficult [36].…”
Section: Discussionmentioning
confidence: 52%
“…Our study also found ALK positive patients with TP53 exon 8 mutation were poorer survival than other mutation types. The TP53 mutant type has been found to be an important factor for gefitinib-induced apoptosis in NSCLC cell lines and reduces gefitinib-induced apoptosis (26). We think that TP53 could have a role as prognostic factor to ALK inhibitors, rather than predictive factor.…”
Section: Discussionmentioning
confidence: 91%
“…13,14 IL-35 may be widely involved in the immune response process in vivo and has become a research hotspot in cytokine research, as it provides a new perspective in the biological treatment of infectious diseases, autoimmune diseases, and tumors. 3,[15][16][17][18][19] Growing evidence now supports a role for IL-35 in tumor occurrence and development. For example, the level of plasma IL-35 was significantly higher in patients with NSCLC than in healthy controls (21.37 ± 11.55 pg/mL vs. 10.09 ± 5.32 pg/mL).…”
Section: Discussionmentioning
confidence: 99%